The Effect of a Traditional Product, Hazelnut-Zante Currant Mixture, on an Animal Model of Autism - Neda Orouji; Mohammad-Reza Zarrindast; Mitra-Sadat Sadat-Shirazi; Amir Hossein Memari; Mehrdad Karimi; Arman Zargaran* (Research Journal of Pharmacognosy, 2025)
Background and objectives: Autism spectrum disorder (ASD) is a complicated disorder. Hazelnut and Zante can be of great importance in controlling autism due to their high antioxidant and anti-inflammatory capacities. Methods: Zante currant was mixed with distilled water and condensed. Hazelnut and honey were added afterwards. The mixture was diluted with distilled water to obtain the final product hazelnut-Zante currant mixture. Twenty-four female rats were used, with pregnant rats divided into two groups: one receiving saline and designated as non-autistic rats, and the other receiving sodium valproate and designated as autistic rats. Offspring from both groups were further divided into subgroups, receiving either tap water or hazelnut-Zante currant mixture from postnatal day 30 to 65. Social interaction and elevated plus maze tests were conducted to assess the sociability and anxiety-like behavior. The prefrontal cortex (PFC) and amygdala were collected for analysis. Results: Administering hazelnut-Zante currant mixture for one month significantly improved sociability and reduced anxiety-like behavior in autistic animals. Autistic rats exhibited elevated levels of aspartate, glutamate, interleukin 1-β, and tumor necrosis factor α (TNF-α) in the brain, along with decreased superoxide dismutase (SOD) levels in the PFC and amygdala. The result did not show notable changes in SOD, interleukin 1-β, and TNF-α levels in either the amygdala or prefrontal cortex. Conclusions: Our findings suggest that this herbal mixture could serve as a promising non-pharmacological candidate for alleviating the behavioral symptoms of ASD.